Vietnam’s Strategic Choice in the Context of US–China Competition - Chaoying Zhang; Serafettin Yilmaz (China Quarterly of International Strategic Studies)
As the US–China rivalry intensifies, countries in Southeast Asia find themselves having to oscillate between the two superpowers. Vietnam is one of those countries forced to make difficult strategic choices in a way that would not undermine its international standing vis-à-vis other regional stakeholders and, where possible, advance its national interests. This paper analyzes the factors influencing Vietnam’s policy within the Vietnam–US–China trilateral interaction. To this end, it compares the internal and external forces that impact Hanoi’s policy-making processes and extrapolates Vietnam’s foreign policy choices against the backdrop of US–China competition.